The Role of the Immune System in Nevirapine-Induced Subclinical Liver Injury of a Rat Model. (15th August 2012) - Bekker, Zanelle; Walubo, Andrew; du Plessis, Jan B.
Abstract : In this study, the role of the immune system in nevirapine- (NVP-) induced subclinical liver injury was investigated by observing for changes of some immune parameters during the initial stages of NVP-induced hepatotoxicity in a rat model. In the acute phase, two test-groups of 10 Sprague-Dawley rats each were administered with bacterial lipopolysaccharide (LPS) or saline (S) intraperitoneally, followed by oral NVP, after which 5 rats from each group were sacrificed at 6 and 24 hours. For the chronic phase, two groups of 15 rats each received daily NVP, and on days 7, 14, and 21, five rats from each group were administered with either LPS or S, followed by that day's NVP dose, and were sacrificed 24 hours later. NVP caused liver injury up to seven days and progressively increased IL-2 and IFN- γ levels and lymphocyte count over the 21 days. NVP-induced liver injury was characterized by apoptosis and degeneration changes, while, for LPS, it was cell swelling, leukostasis, and portal inflammation. Coadministration of NVP and LPS attenuated NVP-induced liver injury. In conclusion, the immune system is involved in NVP toxicity, and the LPS effects may lay the clue to development of therapeutic strategies against NVP-induced hepatotoxicity.